Effects of sprint interval training on ectopic lipids and tissue-specific insulin sensitivity in men with non-alcoholic fatty liver disease - Sargeant, Jack A.; Bawden, Stephen; Aithal, Guruprasad P.; Simpson, Elizabeth J.; Macdonald, Ian A.; Turner, Mark C.; Cegielski, Jessica; Smith, Kenneth; Dorling, James L.; Gowland, Penny A.; Nimmo, Myra A.; King, James A. (Springer, 2018)
Purpose: This study examined the feasibility of sprint interval exercise training (SIT) for men with non-alcoholic fatty liver disease (NAFLD) and its effects on intrahepatic triglyceride (IHTG), insulin sensitivity (hepatic and peripheral), visceral (VAT) and subcutaneous adipose tissue (ScAT). Methods: Nine men with NAFLD (age 41 ± 8 years; BMI 31.7 ± 3.1 kg m−2; IHTG 15.6 ± 8.3%) were assessed at: (1) baseline (2) after a control phase of no intervention (pre-training) and (3) after 6 weeks of SIT (4–6 maximal 30 s cycling intervals, three times per week). IHTG, VAT and ScAT were measured using magnetic resonance spectroscopy or imaging and insulin sensitivity was assessed via dual-step hyperinsulinaemic-euglycaemic clamp with [6,6-D2] glucose tracer. Results: Participants adhered to SIT, completing ≥ 96.7% of prescribed intervals. SIT increased peak oxygen uptake [ V O2peak: + 13.6% (95% CI 8.8–18.2%)] and elicited a relative reduction in IHTG [− 12.4% (− 31.6 to 6.7%)] and VAT [− 16.9% (− 24.4 to − 9.4%); n = 8], with no change in body weight or ScAT. Peripheral insulin sensitivity increased throughout the study (n = 8; significant main effect of phase) but changes from pre- to post-training were highly variable (range − 18.5 to + 58.7%) and not significant (P = 0.09), despite a moderate effect size (g* = 0.63). Hepatic insulin sensitivity was not influenced by SIT. Conclusions: SIT is feasible for men with NAFLD in a controlled laboratory setting and is able to reduce IHTG and VAT in the absence of weight loss.